2009
DOI: 10.1200/jco.2009.23.5622
|View full text |Cite
|
Sign up to set email alerts
|

American Society of Clinical Oncology Clinical Practice Guideline Update on Chemotherapy for Stage IV Non–Small-Cell Lung Cancer

Abstract: The purpose of this article is to provide updated recommendations for the treatment of patients with stage IV non–small-cell lung cancer. A literature search identified relevant randomized trials published since 2002. The scope of the guideline was narrowed to chemotherapy and biologic therapy. An Update Committee reviewed the literature and made updated recommendations. One hundred sixty-two publications met the inclusion criteria. Recommendations were based on treatment strategies that improve overall surviv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
339
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 697 publications
(353 citation statements)
references
References 151 publications
(7 reference statements)
8
339
1
5
Order By: Relevance
“…This differential efficacy based on histology, as well as a significant treatment-by-histology interaction for pemetrexed, was consistently detected across multiple studies [6]. These results led to a recommendation of pemetrexed-cisplatin for first-line treatment of patients with advanced nonsquamous NSCLC [2], [3] and [4].…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…This differential efficacy based on histology, as well as a significant treatment-by-histology interaction for pemetrexed, was consistently detected across multiple studies [6]. These results led to a recommendation of pemetrexed-cisplatin for first-line treatment of patients with advanced nonsquamous NSCLC [2], [3] and [4].…”
Section: Introductionmentioning
confidence: 89%
“…Platinum-based doublet therapy is recommended for first-line treatment of patients with advanced NSCLC, with cisplatin preferred to carboplatin in Europe [2], [3] and [4]. In a large phase III study of pemetrexed-cisplatin versus gemcitabine-cisplatin, in patients with advanced NSCLC of all histologies (referred to here as "JMDB study"), a pre-specified subgroup analysis in patients with nonsquamous NSCLC showed pemetrexed-cisplatin to have superior survival compared with gemcitabine-cisplatin [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Platinum-based chemotherapy is currently recommended as the standard treatment for patients with advanced NSCLC. 5 However, it is unclear whether it should be recommended as the standard regimen for elderly patients with advanced NSCLC. Its efficacy for such a population has been questioned because of the perceived higher risk of toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…5 On the other hand, large elderly-specific randomized trials have recommended that single-agent chemotherapy with a third-generation agent (e.g., vinorelbine, gemcitabine, taxanes) be used for elderly patients with advanced NSCLC. 5 Vinorelbine is a semisynthetic vinca alkaloid, which showed significantly superior survival over best supportive care (median survival time 27 weeks vs. 21 weeks, p = 0.04) in a landmark Phase III trial in elderly patients with advanced NSCLC. 6 Since then, vinorelbine monotherapy has become one of the most important chemotherapy regimens for elderly patients.…”
Section: Introductionmentioning
confidence: 99%